Antioxidant Activity of Aqueous and Ethanolic Extracts of Coconut (Cocos nucifera) Fruit By-Products - Leliana, Lulum; Setyaningsih, Widiastuti; Palma, Miguel; Supriyadi, Supriyadi; Santoso, Umar (MDPI, 2022)
Coconut is widely used as a food source in producing countries, and during consumption, the waste that is generated needs to be reduced through by-products processing to ensure environmental sustainability. This study aimed to assess the functionality of by-products (endoand mesocarp) of coconuts at early and mature stages. The aqueous and ethanolic (50 and 100% ethanol in water) extracts of coconut by-products were evaluated for the DPPH radical scavenging activity and subjected to linoleic acid-β-carotene system assay in contrast with synthetic antioxidants. Ultrasound-producing extract of young coconut mesocarp provided the highest antioxidant activity with a lower IC50 value (117 μg mL−1) than butylhydroxytoluene (BHT, 170 μg mL−1). Based on the linoleic acid-β-carotene system assay, the extract exhibited a higher antioxidant activity (1.25×) than tertiary butylhydroquinone (TBHQ, 200 μg mL−1); and comparable with butylhydroxyanisole (BHA, 250 μg mL−1). Therefore, extracts of coconut by-products, particularly the young mesocarp, can be an alternative natural antioxidant.